2013
DOI: 10.1111/hpb.12133
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of laparoscopic radiofrequency ablation versus systemic therapy alone in the treatment of breast cancer metastasis to the liver

Abstract: This is the first study to compare outcomes in RFA and ST, respectively, in LMBC. The results show that survival after laparoscopic RFA plus ST is better than that after ST alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…39-47 The median survival for this heterogeneous group of NCNN liver metastases patients has been reported to range from 27 to 49 months. 16-18,39-47 In a large multi-institutional study by Adam et al, 460 patients with isolated BCLM who underwent resection experienced a median survival of 45 months and a 5- and 10-year OS of 41% and 22%, respectively. 42 These results were comparable to those obtained with resection of colorectal and neuroendocrine liver metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39-47 The median survival for this heterogeneous group of NCNN liver metastases patients has been reported to range from 27 to 49 months. 16-18,39-47 In a large multi-institutional study by Adam et al, 460 patients with isolated BCLM who underwent resection experienced a median survival of 45 months and a 5- and 10-year OS of 41% and 22%, respectively. 42 These results were comparable to those obtained with resection of colorectal and neuroendocrine liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Although promising results reporting 5-year survival of up to 61% after hepatic resection or ablation have been published in recent case series these studies are limited by their retrospective nature, small cohorts and lack of controls. 4,13-18 …”
Section: Introductionmentioning
confidence: 99%
“…RFA has also been used for the treatment of noncolorectal liver metastases, particularly those without a dominant blood supply from the hepatic artery; those predominantly supplied by the hepatic artery are preferentially treated with chemoembolization. Taşçi et al 46 conducted a retrospective study of patients with liver metastases from breast cancer treated with laparoscopic RFA and reported a median OS rate of 47 months and a 5-year survival rate of 29% following a diagnosis of liver metastases. Pawlik et al 47 reported on outcomes after RFA with or without resection for sarcoma liver metastases and observed 1-, 3-, and 5-year OS rates of 91.2%, 65.4%, and 27.1%, respectively.…”
Section: Noncolorectal Metastasesmentioning
confidence: 99%
“…A recent study compared laparoscopic RFA in BC patients who failed to respond or showed an incomplete response to ST (n = 24) or to ST alone (n = 32): patients were matched by size and number of LiM, and the 2 groups were similar in HR status and chemotherapy exposure. OS after the diagnosis of LiM was 47 months in the RFA group and 9 months in the ST-only group (p = 0.0001) [54]. Skepticism remains over the efficacy of RFA in BC due to the heterogeneity of patient inclusion and selective nature of reporting.…”
Section: Local Treatment Of Selected Disease Sitesmentioning
confidence: 99%